2021
DOI: 10.1111/irv.12847
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine hesitancy and attitudes in Qatar: A national cross‐sectional survey of a migrant‐majority population

Abstract: Background Vaccine hesitancy is a global threat undermining control of preventable infections. Emerging evidence suggests that hesitancy to COVID‐19 vaccination varies globally. Qatar has a unique population with around 90% of the population being economic migrants, and the degree and determinants of hesitancy are not known. Methods This study was carried out to evaluate the degree of vaccine hesitancy and its socio‐demographic and attitudinal determinants across a repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
139
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(186 citation statements)
references
References 27 publications
23
139
9
Order By: Relevance
“…Importantly, although highlighted as a concern in the literature (33,34), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (33,34). Thus, the Norwegian governments implemented campaigns translating vaccination and pandemicrelated information in the native languages of minority groups seems to have been an appropriate precautionary strategy in preventing the development of such forecasted problems.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, although highlighted as a concern in the literature (33,34), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (33,34). Thus, the Norwegian governments implemented campaigns translating vaccination and pandemicrelated information in the native languages of minority groups seems to have been an appropriate precautionary strategy in preventing the development of such forecasted problems.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding that rural residents were more likely to be hesitant toward vaccination is further consistent with findings showing more vaccine resistance among people residing in the suburbs than in cities (Murphy et al, 2021). Importantly, although highlighted as a concern in the literature (Alabdulla et al, 2021;Netfa et al, 2020), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (Alabdulla et al, 2021;Netfa et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, although highlighted as a concern in the literature (Alabdulla et al, 2021;Netfa et al, 2020), the present study found no empirical support for the notion that immigrants display more skepticism toward vaccination compared to natives. This has been a theorized concern assuming less access to public information as a relevant factor (Alabdulla et al, 2021;Netfa et al, 2020). Thus, the Norwegian governments implemented campaigns translating vaccination and pandemic-related information in the native languages of minority groups seems to have been an appropriate precautionary strategy in preventing the development of such forecasted problems.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the survey structure was different to ours and we targeted a specific sector of the Qatari population, the acceptance rates between these two studies are very similar. This suggests that, even after the start of the vaccination campaign in Qatar, vaccine hesitancy persists, as shown by Alabdulla et al [ 14 ] and our data. Similar results have been reported in other Gulf countries.…”
Section: Discussionsupporting
confidence: 85%
“…In the UK, a study by University College London’s Virus Watch showed that the UK acceptance rate increased after the vaccination program had started, with 86% of participant who rejected the vaccine in December 2020 going on to accept taking the vaccine in February 2021 [ 13 ]. A general Qatari population survey conducted by Alabdulla et al from mid-October to mid-November 2020, before the vaccination program started, showed that almost 61% of participants said they would “definitely” or “probably” accept the vaccine [ 14 ]. Although the survey structure was different to ours and we targeted a specific sector of the Qatari population, the acceptance rates between these two studies are very similar.…”
Section: Discussionmentioning
confidence: 99%